Age and growth rate of congeneric tree species (Hymenaea spp. - Leguminosae) inhabiting different tropical biomes - Lcosselli, Guliano M.; Krottenthaler, Stefan; Pitsch, Philipp; Anhuf, Dieter; Ceccantini, Gregório (ERDKUNDE, 2017)
Age and radial growth rate are key data on understanding some aspects of tropical forest dynamics and ecology. In species that produce annual tree rings, tree-ring analysis allows the most precise estimate of these two parameters. The present study assessed the age and radial growth rate of three Hymenaea species inhabiting four of the six biomes found in Brazil. Out of these four biomes, two harbor the largest rainforests in South America, the Amazon Forest on the west and the Atlantic Forest in the east. The Cerrado biome is an open and seasonally drier vegetation found between them and the Pantanal is a wetland in the west. The H. courbaril species inhabits almost the entire Neotropical lowlands while H. parvifolia and H. stigonocarpa are restricted to the Amazon and Cerrado biomes, respectively. To investigate these species dynamics within different biomes, age and radial growth rate were calculated for 217 trees through tree-ring analyses. The oldest H. courbaril and H. parvifolia trees were 316 and 371 years old, respectively, while H. stigonocarpa trees were considerably younger, up to 144 years old. Hymenaea courbaril trees showed the widest variation in average growth rate, from 1.00 to 6.63 mm per year, while the other two species showed a narrower variation from 0.89 to 2.81 mm per year. The studied populations presented distinct trends in the lifetime growth pattern that seems to be related to the biome of provenance. Overall, trees from the Amazon forest showed a trend of increasing growth rate up to about 100 years followed by a decreasing of it, while trees growing in the Pantanal and Atlantic forest showed only decreasing growth rates. In the Cerrado, trees showed a constant pattern of growth rate up to 50 years followed by a clear decline. It is important to highlight that different species of Hymenaea showed similar growth trends within the same biome. In larger trees, the average growth rate is lower in the Cerrado, which is characterized by deeper water tables and more dystrophic soils while the growth rates in the Amazon and Atlantic Forests are 60 % and 79 % higher, respectively. This study represents one of the most comprehensive datasets of trees age and growth rate of tropical congeneric species under such large geographical range.